Polylactic Acid/Poly(vinylpyrrolidone) Co-Electrospun Fibrous Membrane as a Tunable Quercetin Delivery Platform for Diabetic Wounds - Francesca Di Cristo; Anna Valentino; Ilenia De Luca; Gianfranco Peluso; Irene Bonadies; Anna Di Salle; Anna Calarco (MDPI AG, 2023)
Diabetic wound infections (DWI) represent one of the most costly and disruptive complications in diabetic mellitus. The hyperglycemic state induces a persistent inflammation with immunological and biochemical impairments that promotes delayed wound healing processes and wound infection that often results in extended hospitalization and limb amputations. Currently, the available therapeutic options for the management of DWI are excruciating and expensive. Hence, it is essential to develop and improve DWI-specific therapies able to intervene on multiple fronts. Quercetin (QUE) exhibits excellent anti-inflammatory, antioxidant, antimicrobial and wound healing properties, which makes it a promising molecule for the management of diabetic wounds. In the present study, Poly-lactic acid/poly(vinylpyrrolidone) (PP) co-electrospun fibers loaded with QUE were developed. The results demonstrated a bimodal diameter distribution with contact angle starting from 120°/127° and go to 0° in less than 5 s indicating the hydrophilic nature of fabricated samples. The release QUE kinetics, analyzed in simulated wound fluid (SWF), revealed a strong initial burst release, followed by a constant and continuous QUE release. Moreover, QUE-loaded membranes present excellent antibiofilm and anti-inflammatory capacity and significantly reduce the gene expression of M1 markers tumor necrosis factor (TNF)-α, and IL-1β in differentiated macrophages. In conclusion, the results suggested that the prepared mats loaded with QUE could be a hopeful drug-delivery system for the effective treatment of diabetic wound infections.